2013
DOI: 10.2147/dmso.s46341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phyllanthus emblica extract on endothelial dysfunction and biomarkers of oxidative stress in patients with type 2 diabetes mellitus: a randomized, double-blind, controlled study

Abstract: BackgroundIt has been reported that hyperglycemia can induce endothelial dysfunction via increased oxidative stress and that it plays a central role in the development of atherosclerosis and coronary heart disease. Phyllanthus emblica (Emblica officinalis, amla) is known for its antioxidant and antihyperlipidemic activity. The present study compared the effects of an aqueous extract of P. emblica (highly standardized by high-performance liquid chromatography to contain low molecular weight hydrolyzable tannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
(34 reference statements)
2
27
0
Order By: Relevance
“… 24 Another recent study demonstrated a significant decrease of LDL-C and a concomitant increase of HDL-C in 42 subjects with type 2 diabetes supplemented with CAPROS (500 mg, twice daily) for 12 weeks. 12 , 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 Another recent study demonstrated a significant decrease of LDL-C and a concomitant increase of HDL-C in 42 subjects with type 2 diabetes supplemented with CAPROS (500 mg, twice daily) for 12 weeks. 12 , 13…”
Section: Discussionmentioning
confidence: 99%
“… 16 The significant hs-CRP-lowering effect observed in the current study is comparable to earlier studies on CAPROS supplementation. 12 , 13…”
Section: Discussionmentioning
confidence: 99%
“…61 Schiano et al 62 and Mackay et al 63 reported no change in hsCRP and platelet aggregation with ω-3FAs. In previous studies 27,64 carried out in our department, we reported the beneficial effects of PCC and its constituent materials on hsCRP. In the present study, we observed a significant change in hsCRP values at 12 weeks in all three treatment groups.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical studies in humans have proven the hypolipidemic, antioxidant and cardioprotective activities of P. emblica. [27][28][29][30][31][32][33] Shilajit, a rock exudate containing free and chromoprotein-conjugated dibenzo-α-pyrones (urolithins) and fulvic acids as bioactives, finds broad use in Ayurveda for different clinical applications, such as improving cardiovascular health, upregulating collagen and related extracellular matrix protein genes [34][35][36][37][38] Shilajit seems to induce the growth of blood vessels 39 and has a prominent cardioprotective effect. 40 A clinical study with ω-3FA, in combination with another product, to broaden the spectrum of cardiovascular benefits of ω-3FA in T2DM, without increasing the size or cost of the dosage form significantly, is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…[31], infection, iron overload [32], and antioxidant deficiency [33], etc. Oxidative stress can provoke inflammation by activating NF-κB and causing the subsequent generation of pro-inflammatory cytokines (Figure 6) [34].…”
Section: Discussionmentioning
confidence: 99%